Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan Perusahaan Manufaktur Yang Terdaftar Di BEI - Melisa Jayanti, Herlin Tundjung (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study is to analyze the influence of environmental public disclosure, capital structure, firm size, and liquidity on economic performance of manufacturing companies in Indonesia. This research was conducted on manufacturing companies listed on IDX from 2017 to 2019, the samples were selected using purposive sampling method and 14 companies were acquired as valid data. The data collected were processed using EViews program v.10.0.  The results showed that environmental public disclosure, capital structure, and firm size simultaneously have a significant effect on economic performance. Partially, environmental public disclosure has a positive and significant effect on economic performance, capital structure has a negative and significant effect on economic performance, while firm size and liquidity do not have significant effects on economic performance.